ANALISIS EFEKTIVITAS PERUBAHAN ORGANISASI DENGAN MENGGUNAKAN MODEL 7S MCKINSEY DI PT KOMPAS GRAMEDIA GROUP OF RETAIL AND PUBLISHING (GORP) - Astrid Namira Majid (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to analyze the effectiveness of organizational change in the structural aspect that has been carried out by Kompas Gramedia Group of Retail and Publishing (GoRP) through the 7S McKinsey Framework. The informant selection technique in this study was purposive sampling. The research method used is a qualitative approach that uses the principle of Data Triangulation. Data collection techniques that are used in this study are interviews, questionnaires and document studies. The interview technique used is in-depth interviews with informants. in-depth interviews were conducted with the Manager of Organization & Talent Management, Digital Supervisor and Publishing Staff. In this study, it was found that the leadership style of Kompas GoRP, which was directly involved in change and the existence of shared values, had an important role in the success of accepting change. These changes have an impact on the work system, improving employee skills and facilities. However, it has not been seen that the organization provides adequate facilities to meet the high demands. Overall, the effectiveness of the structural changes carried out by Kompas GoRP cannot be seen because it is still in the transition phase.